Intervenção em disfagia orofaríngea neurogênica: uma revisão integrativa - Trindade, Afra Marilia Alves (2022)
Objective: to identify how speech therapy interventions in neurogenic oropharyngeal dysphagia performed in adults and the elderly. Research strategies: electronic search strategies were individually developed for the following databases: Embase, Google Scholar, Medline/PubMed and Web of Science. Selection criteria: all studies with full text availability online, in English, Portuguese or Spanish, in the population of adults aged 18 years and older and/or elderly people who have oropharyngeal dysphagia associated with neurogenic-based diseases were included, with an interventionist approach performed by speech therapy and who answered the guiding question. Data analysis: two reviewers (AMAT and BKV) selected the studies in a three-step process: quantitative analysis of the studies found in the databases using the descriptors as a search strategy; selection of articles by reading titles and abstracts; and full reading and review by evaluators of the studies selected for the construction of the review. Conclusion: we conclude with this study that the speech therapy interventions in neurogenic oropharyngeal dysphagia most commonly found in the literature are: traditional swallowing therapy; neuromuscular electrical stimulation combined; chin flexion exercise against resistance; biofeedback EMG’s; and expiratory muscle strength training; Shaker maneuver; tongue strength training; swallowing with effort; Mendelsohn maneuver and voice training combined.